Archives : principles and practices - Millar, Laura, 1959- (New York : Neal-Schuman Publishers, 2010)
"Divided into four easy-to-follow parts, this authoritative handbook from experienced archivist Laura A. Millar addresses the contextual, s trategic, operational, and practical issues associated with creating an archival program. Millar covers the critical topics you need to know t o improve your professional skills, including: Establishing principles, policies, and procedures; managing day-to-day operations; caring for d ifferent types of archival materials; enhancing outreach and public acc ess; ensuring the growth and sustainability of the institution and its services. This new title is essential for anyone involved in collecting , curating, and managing archives because the accessible, jargon-free l anguage provides both novice and experienced professionals with a clear outline of all the fundamental principles and practices in the field"- -Publisher's description.
What are archives? -- Archival institutions : creatures of history a nd culture -- Archival service : a matter of trust -- Protecting archiv es -- Provenance, original order and respect des fonds -- Appraising an d acquiring archives -- Arranging and describing archives -- Making arc hives available -- The challenge of digital archives.
Includes bibliographical references and index.
Keywords: Archives-- -- Administration; Archival materials -- Management; Archival materials -- Conservation and restoration; Cataloging of archival materials; Archives; Cataloging; Library Collection Development